A base film for puncture-resistant composite current collector and preparation method thereof

Through the design of a specific structure and raw material ratio in the base film, a high -performance puncture -resistant composite streaming base film is formed, which solves the problem of internal short circuits that are prone to occur under stress. Better performance and longer service life.

CN118852705BActive Publication Date: 2025-01-28扬州博恒新能源材料科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411280297.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-28
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing base film for composite fluid collecting is prone to internal short circuit under mechanical, thermal and electrical stresses, resulting in thermal runaway and safety accidents of the battery, and its puncture resistance is insufficient.

Method used

The base film for a piercing composite stream of the top -to -bottom structure is adopted from the top -to -bottom structure. Composition, the upper surface layer and the lower surface layer are made of specific chemicals according to the raw material of the weight calculation, and the primary membrane is formed by dual screw extrusion, flowing the casting, and two -way stretching process. Corporation.

Benefits of technology

Improve the flame retardant performance, heat resistance and aging performance of the base membrane, and the resistance of puncture resistance, enhance the adhesion performance with the metal layer, extend the service life, and improve the preparation efficiency and good product rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a puncture-resistant composite current collector base film and a preparation method thereof, and relates to the technical field of current collectors, and includes an upper surface layer, a core layer and a lower surface layer from top to bottom, wherein the core layer is made of the following raw materials: PET resin, polyphosphoric acid, phosphorus pentoxide, antioxidant, coupling agent, filler, linear low-density polyethylene, compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials: 2-acrylamide-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxane, 2,4-diphenyl-4-methyl-1-pentene, ester containing unsaturated olefinic bonds, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine, initiator, 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt. The base film has good flame retardancy, excellent heat aging resistance and puncture resistance, good surface adhesion, safe use, environmental protection and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of current collectors, and in particular to a base film for a puncture-resistant composite current collector and a preparation method thereof. Background Art

[0002] With the continuous development of the lithium-ion battery industry, people are increasingly pursuing high energy density and lightweight batteries. As an important component of the battery, the current collector plays a key role in reducing the internal resistance of lithium-ion batteries and improving the coulombic efficiency, cycle stability and rate performance of the battery. However, traditional current collectors are mostly metal current collectors, which are very heavy. When they are damaged by mechanical stress (especially extrusion, puncture, impact), thermal stress or electrical stress, internal short circuits are also prone to occur, causing thermal runaway of the battery and leading to safety accidents. It is in this situation that composite current collectors came into being, and its appearance has attracted widespread attention in the industry.

[0003] The composite current collector uses a polymer film as a base film, and is prepared by attaching metal materials to the front and back of the base film to form a metal layer through methods such as physical vapor deposition. The base film is one of the key components of the composite current collector, and its performance directly affects the quality of the composite current collector. The base film for traditional composite current collectors is usually PET or PP. PET contains a large number of ester groups, which is prone to swelling, causing the metal layer and the base film layer in the composite current collector to fall off, thereby affecting the positive and negative electrode interfaces inside the battery, resulting in poor electrical performance of the battery, and also affecting the safety of the battery. PP can alleviate the swelling problem to a certain extent, but the PP material is prone to defects such as insufficient bonding with the metal layer and falling off of the metal layer on the surface of the composite current collector due to the almost absence of oxygen-containing groups and other non-CH groups in its molecular structure. In addition, the base films for composite current collectors on the market generally have the defect of insufficient puncture resistance, making it difficult to ensure the safety of the battery under extreme conditions such as collision and impact.

[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN115447246B discloses a swelling-resistant polyester composite film and its preparation method and application. The swelling-resistant polyester composite film includes a core layer, a surface layer A and a surface layer B, and the surface layer A and the surface layer B are respectively located on the two side surfaces of the core layer; in terms of mass percentage, the raw materials of the surface layer A and the surface layer B independently include: 88% to 97% polyester material and 3% to 12% additives, and the raw materials of the core layer include: 95% to 99% polyester material and 1% to 5% additives. The application regulates the content of nucleating agent in the surface layer A, the core layer and the surface layer B, so that the surface layer A and the surface layer B have relatively high crystallinity, providing solvent resistance for the polyester composite film, and the core layer has a relatively low crystallinity to provide flexibility, which is conducive to reducing the film breakage rate in the film making process and ensuring the stable production of the polyester composite film. The composite current collector with the polyester composite film as the base film has a certain solvent resistance in its surface layer A and surface layer B, which can prevent the electrolyte from penetrating into the polyester composite film and destroying its structure, thereby improving the stability of the composite current collector. However, the flame retardancy, heat aging resistance and puncture resistance of the material still need to be further improved.

[0005] It can be seen that the development of a puncture-resistant composite current collector base film and its preparation method which have good flame retardancy, excellent heat aging resistance and puncture resistance, good surface adhesion, safe use, environmental protection and long life meet the market demand, have broad market value and application prospects, and are of great significance to promoting the development of the field of composite current collector base films. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a base film for a puncture-resistant composite current collector having good flame retardancy, excellent heat aging resistance and puncture resistance, good surface adhesion, safe use, environmental protection and long service life, and a preparation method thereof.

[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a base film for a puncture-resistant composite current collector, which includes an upper surface layer, a core layer and a lower surface layer from top to bottom, wherein the core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.1-0.3 parts of polyphosphoric acid, 0.3-0.5 parts of phosphorus pentoxide, 0.3-0.5 parts of antioxidant, 2-4 parts of coupling agent, 15-25 parts of filler, 10-20 parts of linear low-density polyethylene, and 3-5 parts of compatibilizer; the upper surface layer and the lower surface layer are independently The invention is prepared from the following raw materials in parts by weight: 6-8 parts of 2-acrylamido-2-methylpropanesulfonic acid, 3-5 parts of 2,4,6-trivinyl cycloboroxane, 3-5 parts of 2,4-diphenyl-4-methyl-1-pentene, 10-15 parts of an ester containing an unsaturated olefinic bond, 2-4 parts of allyl triphenylphosphine bromide, 0.5-0.8 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.1-0.3 parts of an initiator, and 0.3-0.5 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt.

[0008] Preferably, the thickness of the upper surface layer and the lower surface layer is the same; the thickness of the core layer is 2-4 μm; and the total thickness of the base film is 5-10 μm.

[0009] Preferably, the brand of the PET resin is PET CZ-333, which is provided by Jiangyin Xingye.

[0010] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 168, and antioxidant 1076.

[0011] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.

[0012] Preferably, the filler is a mixture of aluminum hydroxide flame retardant VK-LA50, graphene, and carbon fiber in a mass ratio of 1:(3-5):2.

[0013] Preferably, the average diameter of the carbon fiber is 3-6 μm and the length is 1-3 mm.

[0014] Preferably, there is no special requirement for the source of the graphene. In one embodiment of the present invention, the graphene is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104591178B.

[0015] Preferably, the linear low-density polyethylene is selected from linear low-density polyethylene with a grade of DFDA9030, which is provided by Sinopec.

[0016] Preferably, the compatibilizer is the compatibilizer CMG9801 provided by Jiayirong Polymer (Shanghai) Co., Ltd.

[0017] Preferably, the ester containing unsaturated olefinic bonds is at least one of hydroxyethyl acrylate and 2-methoxyethyl acrylate.

[0018] Preferably, the initiator is azobisisobutyronitrile.

[0019] Another object of the present invention is to provide a method for preparing the base film for the puncture-resistant composite current collector, comprising the following steps:

[0020] Step S1, after the raw materials of the core layer are uniformly mixed according to the weight proportions, the raw materials are extruded and casted by a twin-screw extruder in sequence to form a sheet; the sheet is stretched by a biaxial stretching process to form a primary film;

[0021] Step S2, after uniformly mixing 2-acrylamido-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxine, 2,4-diphenyl-4-methyl-1-pentene, an ester containing an unsaturated olefinic bond, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine and an initiator, respectively apply the mixture on the upper surface and the lower surface of the primary film; and place the mixture at 60-70° C. for curing for 1-3 hours, and then heat-treat the mixture at 175-185° C. for 30-50 minutes to obtain a surface-modified primary film;

[0022] Step S3, immersing the surface modified primary film in an aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt at 50-60° C. for 20-30 hours, taking it out, washing it with water for 3-6 times, and then drying it to obtain a base film for a puncture-resistant composite current collector.

[0023] Preferably, the die head temperature of the twin-screw extruder in step S1 is 230-260°C.

[0024] Preferably, the biaxial stretching process in step S1 is specifically as follows: the stretching temperature is 115-125° C., the stretching rate is 110-80 mm / s, the heat setting temperature is 210-230° C., and the stretching ratio is 4:1.

[0025] Preferably, the mass percentage concentration of the aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt in step S3 is 10-20%.

[0026] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0027] (1) The method for preparing the base film for the puncture-resistant composite current collector disclosed in the present invention can be realized by conventional operations and equipment, with low capital investment, low energy consumption, high preparation efficiency and yield rate, convenient operation, low labor intensity, and little impact on the environment. It is suitable for industrial production and has high promotion and application value.

[0028] (2) The base film for the puncture-resistant composite current collector disclosed in the present invention includes an upper surface layer, a core layer and a lower surface layer from top to bottom. Through such a structural design, the base film can combine the advantages of each layer structure to give the product better performance;

[0029] The core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.1-0.3 parts of polyphosphoric acid, 0.3-0.5 parts of phosphorus pentoxide, 0.3-0.5 parts of antioxidant, 2-4 parts of coupling agent, 15-25 parts of filler, 10-20 parts of linear low-density polyethylene, and 3-5 parts of compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials in parts by weight: 2-acrylamide-2-methylacrylamide 6-8 parts of sulfonic acid, 3-5 parts of 2,4,6-trivinyl boroxane, 3-5 parts of 2,4-diphenyl-4-methyl-1-pentene, 10-15 parts of ester containing unsaturated olefinic bonds, 2-4 parts of allyl triphenylphosphonium bromide, 0.5-0.8 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.1-0.3 parts of initiator, 0.3-0.5 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt. Through the reasonable selection of the types and dosage ratios of the raw materials for the preparation of each layer, they can cooperate with each other and work together to give the product good flame retardancy, excellent heat aging resistance and puncture resistance, good surface adhesion, safe use, environmental protection and long life.

[0030] (3) The base film for the puncture-resistant composite current collector disclosed in the present invention has a core layer made of a blend of PET resin and linear low-density polyethylene, and is reinforced by fillers. The combined effect can effectively improve the puncture resistance performance; after the upper surface layer and the lower surface layer are cured, amide groups, cycloboroxine, phenyl, ester groups, triphenylphosphine and phenoxazine groups are simultaneously introduced into their molecular structures. These groups, under the multiple effects of electronic effect, steric effect and conjugation effect, can not only improve the adhesion between them and the metal and between them and the core layer; they can also improve the flame retardancy, heat aging resistance and puncture resistance of the product, thereby extending its service life. 2,4,6-Trivinyl cycloboroxine contains multiple unsaturated olefinic bonds. After curing, an interpenetrating network cross-linking structure will be formed on the surface, which can further improve the above-mentioned properties and also play a role in reducing swelling. During the preparation process, 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt can undergo ion exchange reaction with the structural unit introduced by allyl triphenylphosphonium bromide to form an ionic cross-linking structure, thereby increasing the cross-linking density. Moreover, the introduced fluorinated phenyl sulfone structure cooperates with other groups to further improve the above-mentioned properties.

[0031] (4) In the base film for the puncture-resistant composite current collector disclosed in the present invention, the structural units introduced by 2-acrylamido-2-methylpropanesulfonic acid in the upper surface layer and the lower surface layer can chemically react with the benzene rings on the core layer PET resin under the catalytic action of polyphosphoric acid and phosphorus pentoxide, thereby effectively improving the interaction between the layers, avoiding delamination, improving the product stability, and effectively extending its service life.

[0032] (5) The base film for the puncture-resistant composite current collector disclosed in the present invention is not easily damaged during the preparation process and is easy to process and shape through the reasonable selection of preparation process parameters and steps, thereby ensuring that the final product has the advantages of good flame retardancy, excellent heat aging resistance and puncture resistance, good surface adhesion, safe use, environmental protection and long service life. DETAILED DESCRIPTION

[0033] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0034] Example 1, a base film for a puncture-resistant composite current collector, comprising an upper surface layer, a core layer and a lower surface layer from top to bottom, wherein the core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.1 parts of polyphosphoric acid, 0.3 parts of phosphorus pentoxide, 0.3 parts of antioxidant, 2 parts of coupling agent, 15 parts of filler, 10 parts of linear low-density polyethylene, and 3 parts of compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials in parts by weight The raw materials in parts are as follows: 6 parts of 2-acrylamido-2-methylpropanesulfonic acid, 3 parts of 2,4,6-trivinyl cycloboroxane, 3 parts of 2,4-diphenyl-4-methyl-1-pentene, 10 parts of ester containing unsaturated olefinic bonds, 2 parts of allyl triphenylphosphine bromide, 0.5 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.1 parts of initiator, and 0.3 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt.

[0035] The thickness of the upper surface layer and the lower surface layer is the same; the thickness of the core layer is 4 μm; the total thickness of the base film is 6 μm; the brand of the PET resin is PET CZ-333, provided by Jiangyin Xingye; the antioxidant is antioxidant 1010; the coupling agent is silane coupling agent KH550; the filler is a mixture of aluminum hydroxide flame retardant VK-LA50, graphene, and carbon fiber in a mass ratio of 1:3:2; the average diameter of the carbon fiber is 3 μm and the length is 1 mm; the graphene is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104591178B.

[0036] The linear low-density polyethylene is selected from linear low-density polyethylene with a grade of DFDA9030, which is provided by Sinopec; the compatibilizer is the compatibilizer CMG9801 provided by Jiayirong Polymer (Shanghai) Co., Ltd.; the ester containing unsaturated olefinic bonds is hydroxyethyl acrylate; and the initiator is azobisisobutyronitrile.

[0037] A method for preparing the base film for the puncture-resistant composite current collector comprises the following steps:

[0038] Step S1, after the raw materials of the core layer are uniformly mixed according to the weight proportions, the raw materials are extruded and casted by a twin-screw extruder in sequence to form a sheet; the sheet is stretched by a biaxial stretching process to form a primary film;

[0039] Step S2, 2-acrylamido-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxine, 2,4-diphenyl-4-methyl-1-pentene, ester containing unsaturated olefinic bonds, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine and an initiator are mixed evenly, and then coated on the upper surface and the lower surface of the primary film respectively; and cured at 60° C. for 1 hour, and then heat treated at 175° C. for 30 minutes to obtain a surface-modified primary film;

[0040] Step S3, immersing the surface-modified primary film in an aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt at 50° C. for 20 hours, taking it out, washing it with water for 3 times, and then drying it to obtain a base film for a puncture-resistant composite current collector.

[0041] The die head temperature of the twin-screw extruder in step S1 is 230°C; the biaxial stretching process in step S1 is specifically as follows: the stretching temperature is 115°C, the stretching rate is 110 mm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1.

[0042] The mass percentage concentration of the aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt in step S3 is 10%.

[0043] Example 2, a base film for a puncture-resistant composite current collector, comprising an upper surface layer, a core layer and a lower surface layer from top to bottom, wherein the core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.15 parts of polyphosphoric acid, 0.35 parts of phosphorus pentoxide, 0.35 parts of antioxidant, 2.5 parts of coupling agent, 17 parts of filler, 13 parts of linear low-density polyethylene, and 3.5 parts of compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials in parts by weight The raw materials are: 6.5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 3.5 parts of 2,4,6-trivinyl boroxine, 3.5 parts of 2,4-diphenyl-4-methyl-1-pentene, 12 parts of ester containing unsaturated olefinic bonds, 2.5 parts of allyl triphenylphosphine bromide, 0.6 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.15 parts of initiator, and 0.35 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt.

[0044] The thickness of the upper surface layer and the lower surface layer is the same; the thickness of the core layer is 4 μm; the total thickness of the base film is 6 μm; the brand of the PET resin is PET CZ-333, provided by Jiangyin Xingye; the antioxidant is antioxidant 168; the coupling agent is silane coupling agent KH560; the filler is a mixture of aluminum hydroxide flame retardant VK-LA50, graphene, and carbon fiber in a mass ratio of 1:3.5:2; the average diameter of the carbon fiber is 4 μm and the length is 1.5 mm; the graphene is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104591178B.

[0045] The linear low-density polyethylene is selected from linear low-density polyethylene with a grade of DFDA9030, which is provided by Sinopec; the compatibilizer is the compatibilizer CMG9801 provided by Jiayirong Polymer (Shanghai) Co., Ltd.; the ester containing unsaturated olefinic bonds is 2-methoxyethyl acrylate; and the initiator is azobisisobutyronitrile.

[0046] A method for preparing the base film for the puncture-resistant composite current collector comprises the following steps:

[0047] Step S1, after the raw materials of the core layer are uniformly mixed according to the weight proportions, the raw materials are extruded and casted by a twin-screw extruder in sequence to form a sheet; the sheet is stretched by a biaxial stretching process to form a primary film;

[0048] Step S2, after uniformly mixing 2-acrylamido-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxine, 2,4-diphenyl-4-methyl-1-pentene, an ester containing an unsaturated olefinic bond, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine and an initiator, respectively apply the mixture on the upper surface and the lower surface of the primary film; and place the mixture at 63° C. for curing for 1.5 h, and then heat-treat the mixture at 178° C. for 35 min to obtain a surface-modified primary film;

[0049] Step S3, immersing the surface modified primary film in an aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt at 53° C. for 23 hours, taking it out, washing it with water for 4 times, and then drying it to obtain a base film for a puncture-resistant composite current collector.

[0050] The die head temperature of the twin-screw extruder in step S1 is 240°C; the biaxial stretching process in step S1 is specifically as follows: the stretching temperature is 117°C, the stretching rate is 100 mm / s, the heat setting temperature is 215°C, and the stretching ratio is 4:1.

[0051] The mass percentage concentration of the aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt in step S3 is 13%.

[0052] Example 3, a base film for a puncture-resistant composite current collector, comprising an upper surface layer, a core layer and a lower surface layer from top to bottom, wherein the core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.2 parts of polyphosphoric acid, 0.4 parts of phosphorus pentoxide, 0.4 parts of antioxidant, 3 parts of coupling agent, 20 parts of filler, 15 parts of linear low-density polyethylene, and 4 parts of compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials in parts by weight The raw materials are as follows: 7 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4 parts of 2,4,6-trivinyl cycloboroxane, 4 parts of 2,4-diphenyl-4-methyl-1-pentene, 13 parts of ester containing unsaturated olefinic bonds, 3 parts of allyl triphenylphosphine bromide, 0.65 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.2 parts of initiator, and 0.4 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt.

[0053] The thickness of the upper surface layer and the lower surface layer is the same; the thickness of the core layer is 4 μm; the total thickness of the base film is 6 μm; the brand of the PET resin is PET CZ-333, provided by Jiangyin Xingye; the antioxidant is antioxidant 1076; the coupling agent is silane coupling agent KH570; the filler is a mixture of aluminum hydroxide flame retardant VK-LA50, graphene, and carbon fiber in a mass ratio of 1:4:2; the average diameter of the carbon fiber is 4.5 μm and the length is 2 mm; the graphene is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104591178B; the linear low-density polyethylene is selected from linear low-density polyethylene with a brand of DFDA9030, provided by Sinopec.

[0054] The compatibilizer is the compatibilizer CMG9801 provided by Jiayirong Polymer (Shanghai) Co., Ltd.; the ester containing unsaturated olefinic bonds is hydroxyethyl acrylate; and the initiator is azobisisobutyronitrile.

[0055] A method for preparing the base film for the puncture-resistant composite current collector comprises the following steps:

[0056] Step S1, after the raw materials of the core layer are uniformly mixed according to the weight proportions, the raw materials are extruded and casted by a twin-screw extruder in sequence to form a sheet; the sheet is stretched by a biaxial stretching process to form a primary film;

[0057] Step S2, after uniformly mixing 2-acrylamido-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxine, 2,4-diphenyl-4-methyl-1-pentene, an ester containing an unsaturated olefinic bond, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine and an initiator, respectively apply the mixture on the upper surface and the lower surface of the primary film; and place the mixture at 65° C. for curing for 2 h, and then heat-treat the mixture at 180° C. for 40 min to obtain a surface-modified primary film;

[0058] Step S3, immersing the surface-modified primary film in an aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt at 55° C. for 25 hours, taking it out, washing it with water for 5 times, and then drying it to obtain a base film for a puncture-resistant composite current collector.

[0059] The die head temperature of the twin-screw extruder in step S1 is 245°C; the biaxial stretching process in step S1 is specifically as follows: the stretching temperature is 120°C, the stretching rate is 95mm / s, the heat setting temperature is 220°C, and the stretching ratio is 4:1.

[0060] The mass percentage concentration of the aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt in step S3 is 15%.

[0061] Example 4, a base film for a puncture-resistant composite current collector, comprising an upper surface layer, a core layer and a lower surface layer from top to bottom, wherein the core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.25 parts of polyphosphoric acid, 0.45 parts of phosphorus pentoxide, 0.45 parts of antioxidant, 3.5 parts of coupling agent, 23 parts of filler, 18 parts of linear low-density polyethylene, and 4.5 parts of compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials in parts by weight The raw materials are: 7.5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4.5 parts of 2,4,6-trivinyl cycloboroxane, 4.5 parts of 2,4-diphenyl-4-methyl-1-pentene, 14 parts of ester containing unsaturated olefinic bonds, 3.5 parts of allyl triphenylphosphine bromide, 0.75 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.25 parts of initiator, and 0.45 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt.

[0062] The thickness of the upper surface layer and the lower surface layer is the same; the thickness of the core layer is 4 μm; the total thickness of the base film is 6 μm; the grade of the PET resin is PET CZ-333, provided by Jiangyin Xingye; the antioxidant is a mixture of antioxidant 1010, antioxidant 168, and antioxidant 1076 in a mass ratio of 1:2:1; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 2:3:5; the filler is a mixture of aluminum hydroxide flame retardant VK-LA50, graphene, and carbon fiber in a mass ratio of 1:4.5:2; the average diameter of the carbon fiber is 5.5μm and the length is 2.5mm; the graphene is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104591178B; the linear low-density polyethylene is selected from linear low-density polyethylene with a grade of DFDA9030, provided by Sinopec.

[0063] The compatibilizer is the compatibilizer CMG9801 provided by Jiayirong Polymer (Shanghai) Co., Ltd.; the ester containing unsaturated olefinic bonds is a mixture of hydroxyethyl acrylate and 2-methoxyethyl acrylate in a mass ratio of 3:5; and the initiator is azobisisobutyronitrile.

[0064] A method for preparing the base film for the puncture-resistant composite current collector comprises the following steps:

[0065] Step S1, after the raw materials of the core layer are uniformly mixed according to the weight proportions, the raw materials are extruded and casted by a twin-screw extruder in sequence to form a sheet; the sheet is stretched by a biaxial stretching process to form a primary film;

[0066] Step S2, 2-acrylamido-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxine, 2,4-diphenyl-4-methyl-1-pentene, ester containing unsaturated olefinic bonds, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine and an initiator are mixed evenly, and then coated on the upper surface and the lower surface of the primary film respectively; and cured at 68° C. for 2.5 hours, and then heat treated at 183° C. for 45 minutes to obtain a surface-modified primary film;

[0067] Step S3, immersing the surface-modified primary film in an aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt at 58° C. for 28 hours, taking it out, washing it with water for 5 times, and then drying it to obtain a base film for a puncture-resistant composite current collector.

[0068] The die head temperature of the twin-screw extruder in step S1 is 255°C; the biaxial stretching process in step S1 is specifically as follows: the stretching temperature is 123°C, the stretching rate is 85mm / s, the heat setting temperature is 225°C, and the stretching ratio is 4:1.

[0069] The mass percentage concentration of the aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt in step S3 is 18%.

[0070] Example 5, a base film for a puncture-resistant composite current collector, comprising an upper surface layer, a core layer and a lower surface layer from top to bottom, wherein the core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.3 parts of polyphosphoric acid, 0.5 parts of phosphorus pentoxide, 0.5 parts of antioxidant, 4 parts of coupling agent, 25 parts of filler, 20 parts of linear low-density polyethylene, and 5 parts of compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials in parts by weight The raw materials in parts are as follows: 8 parts of 2-acrylamido-2-methylpropanesulfonic acid, 5 parts of 2,4,6-trivinyl cycloboroxane, 5 parts of 2,4-diphenyl-4-methyl-1-pentene, 15 parts of ester containing unsaturated olefinic bonds, 4 parts of allyl triphenylphosphonium bromide, 0.8 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.3 parts of initiator, and 0.5 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt.

[0071] The thickness of the upper surface layer and the lower surface layer is the same; the thickness of the core layer is 4 μm; the total thickness of the base film is 6 μm; the brand of the PET resin is PET CZ-333, provided by Jiangyin Xingye; the antioxidant is antioxidant 1010; the coupling agent is silane coupling agent KH560; the filler is a mixture of aluminum hydroxide flame retardant VK-LA50, graphene, and carbon fiber in a mass ratio of 1:5:2; the average diameter of the carbon fiber is 6 μm and the length is 3 mm; the graphene is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104591178B; the linear low-density polyethylene is selected from linear low-density polyethylene with a brand of DFDA9030, provided by Sinopec.

[0072] The compatibilizer is the compatibilizer CMG9801 provided by Jiayirong Polymer (Shanghai) Co., Ltd.; the ester containing unsaturated olefinic bonds is hydroxyethyl acrylate; and the initiator is azobisisobutyronitrile.

[0073] A method for preparing the base film for the puncture-resistant composite current collector comprises the following steps:

[0074] Step S1, after the raw materials of the core layer are uniformly mixed according to the weight proportions, the raw materials are extruded and casted by a twin-screw extruder in sequence to form a sheet; the sheet is stretched by a biaxial stretching process to form a primary film;

[0075] Step S2, after uniformly mixing 2-acrylamido-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxine, 2,4-diphenyl-4-methyl-1-pentene, an ester containing an unsaturated olefinic bond, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine and an initiator, respectively apply the mixture on the upper surface and the lower surface of the primary film; and place the mixture at 70° C. for curing for 3 h, and then heat-treat the mixture at 185° C. for 50 min to obtain a surface-modified primary film;

[0076] Step S3, immersing the surface-modified primary film in an aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt at 60° C. for 30 hours, taking it out, washing it with water for 6 times, and then drying it to obtain a base film for a puncture-resistant composite current collector.

[0077] The die head temperature of the twin-screw extruder in step S1 is 260°C; the biaxial stretching process in step S1 is specifically as follows: the stretching temperature is 125°C, the stretching rate is 80 mm / s, the heat setting temperature is 230°C, and the stretching ratio is 4:1.

[0078] The mass percentage concentration of the aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt in step S3 is 20%.

[0079] Comparative Example 1, a base film for a puncture-resistant composite current collector, is basically the same as Example 1, except that PET resin is used instead of linear low-density polyethylene, and 10-(4-vinylphenyl)-10H-phenoxazine is not added.

[0080] Comparative Example 2, a base film for a puncture-resistant composite current collector, is substantially the same as Example 1, except that allyl triphenylphosphine bromide and 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt are not added.

[0081] In order to further illustrate the beneficial technical effects of the base film for the puncture-resistant composite current collector involved in each embodiment of the present invention, relevant performance tests were performed on the base film for the puncture-resistant composite current collector involved in Examples 1-5 and Comparative Examples 1-2; the test method is as follows:

[0082] (1) Puncture resistance: Puncture resistance strength test is carried out according to GB / T 37841-2019.

[0083] (2) Heat aging resistance: The base film products for each puncture-resistant composite current collector were placed in hot air at 85°C for artificial accelerated aging for 168 hours. After cooling to room temperature, the puncture resistance strength was measured again. The heat aging resistance performance was measured by the retention rate of the puncture resistance strength. The larger the value, the better the heat aging resistance.

[0084] (3) Flame retardancy: tested according to UL94 standard.

[0085] (4) Swelling degree: The base film for the puncture-resistant composite current collector prepared in each example was cut into samples of 20 cm × 20 cm in size, and the circumference of the sample was recorded as C1. The samples were then immersed in an electrolyte at 65°C for 48 h. The circumference of the sample after immersion was recorded as C2. The swelling degree SD of the sample was calculated according to the following formula: SD = (C2-C1) / C1×100%, where the electrolyte was a mixture of ethylene carbonate, diethyl carbonate, and methyl ethyl carbonate in a mass ratio of 1:2:1.

[0086] (5) Adhesion between the base film and the metal conductive layer in the composite current collector: The base films of each example were placed in a magnetron sputtering chamber, and aluminum metal with a purity of 99.99% was used as the target material and argon gas was used as the gas source. By magnetron sputtering in the magnetron sputtering chamber, a 1200 nm thick aluminum metal layer was plated on both sides of the base film of the puncture-resistant composite current collector in each example along the thickness direction to obtain a composite current collector; a layer of Permacel P-94 double-sided tape was adhered to a 1 mm thick aluminum foil, the composite current collector was adhered on the double-sided tape, and a layer of ethylene acrylic acid copolymer film (DuPont Nurcel0903, thickness of 50 μm) was covered on the composite current collector, and then a 1.3×10 5 N / m 2, hot pressing at 120°C for 10s, cooling to room temperature, and cutting into small strips of 150mm×15mm; finally, the ethylene acrylic acid copolymer film of the small sample strip is fixed on the upper fixture of the tensile machine, and the rest is fixed on the lower fixture. After fixation, the two are peeled off at an angle of 180° and a speed of 100mm / min to test the peeling force, which is the bonding force between the base film and the metal conductive layer in the composite current collector.

[0087]

[0088] As can be seen from Table 1, the base film for the puncture-resistant composite current collector involved in each embodiment of the present invention has better puncture resistance, more excellent heat aging resistance, flame retardancy, resistance to electrolyte swelling and surface adhesion than the comparative example products, and the combined use of linear low-density polyethylene, 10-(4-vinylphenyl)-10H-phenoxazine, allyl triphenylphosphine bromide and 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt is beneficial to improving the above properties.

[0089] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A base film for a puncture-resistant composite current collector, characterized in that: The upper surface layer, the core layer and the lower surface layer are sequentially included from top to bottom, wherein the core layer is made of the following raw materials in parts by weight: 80 parts of PET resin, 0.1-0.3 parts of polyphosphoric acid, 0.3-0.5 parts of phosphorus pentoxide, 0.3-0.5 parts of antioxidant, 2-4 parts of coupling agent, 15-25 parts of filler, 10-20 parts of linear low-density polyethylene, and 3-5 parts of compatibilizer; the upper surface layer and the lower surface layer are independently made of the following raw materials in parts by weight: 6-8 parts of 2-acrylamido-2-methylpropanesulfonic acid , 3-5 parts of 2,4,6-trivinyl boroxine, 3-5 parts of 2,4-diphenyl-4-methyl-1-pentene, 10-15 parts of an ester containing unsaturated olefinic bonds, 2-4 parts of allyl triphenylphosphonium bromide, 0.5-0.8 parts of 10-(4-vinylphenyl)-10H-phenoxazine, 0.1-0.3 parts of an initiator, and 0.3-0.5 parts of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt; the ester containing unsaturated olefinic bonds is at least one of hydroxyethyl acrylate and 2-methoxyethyl acrylate; The method for preparing the base film for the puncture-resistant composite current collector comprises the following steps: Step S1, after the raw materials of the core layer are uniformly mixed according to the weight proportions, the raw materials are extruded and casted by a twin-screw extruder in sequence to form a sheet; the sheet is stretched by a biaxial stretching process to form a primary film; Step S2, after uniformly mixing 2-acrylamido-2-methylpropanesulfonic acid, 2,4,6-trivinyl boroxine, 2,4-diphenyl-4-methyl-1-pentene, an ester containing an unsaturated olefinic bond, allyl triphenylphosphine bromide, 10-(4-vinylphenyl)-10H-phenoxazine and an initiator, respectively apply the mixture on the upper surface and the lower surface of the primary film; and place the mixture at 60-70° C. for curing for 1-3 hours, and then heat-treat the mixture at 175-185° C. for 30-50 minutes to obtain a surface-modified primary film; Step S3, immersing the surface modified primary film in an aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt at 50-60° C. for 20-30 hours, taking it out, washing it with water for 3-6 times, and then drying it to obtain a base film for a puncture-resistant composite current collector.

2. The base film for the puncture-resistant composite current collector according to claim 1, characterized in that: The thickness of the upper surface layer and the lower surface layer is the same; the thickness of the core layer is 2-4 μm; and the total thickness of the base film is 5-10 μm.

3. The base film for the puncture-resistant composite current collector according to claim 1, characterized in that: The brand of the PET resin is PET CZ-333; the antioxidant is at least one of antioxidant 1010, antioxidant 168, and antioxidant 1076.

4. The base film for the puncture-resistant composite current collector according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570; the filler is a mixture of aluminum hydroxide flame retardant VK-LA50, graphene, and carbon fiber in a mass ratio of 1:(3-5):

2.

5. The base film for the puncture-resistant composite current collector according to claim 4, characterized in that: The average diameter of the carbon fiber is 3-6 μm, and the length is 1-3 mm; the linear low-density polyethylene is selected from the linear low-density polyethylene with the brand number DFDA9030.

6. The base film for the puncture-resistant composite current collector according to claim 1, characterized in that: The compatibilizer is compatibilizer CMG9801; the initiator is azobisisobutyronitrile.

7. The base film for the puncture-resistant composite current collector according to claim 1, characterized in that: The die head temperature of the twin-screw extruder in step S1 is 230-260°C.

8. The base film for the puncture-resistant composite current collector according to claim 1, characterized in that: The biaxial stretching process in step S1 is specifically as follows: the stretching temperature is 115-125° C., the stretching rate is 110-80 mm / s, the heat setting temperature is 210-230° C., and the stretching ratio is 4:

1.

9. The base film for a puncture-resistant composite current collector according to claim 1, characterized in that: The mass percentage concentration of the aqueous solution of 3,3'-disulfonic acid-4,4'-difluorophenyl sulfone disodium salt in step S3 is 10-20%.

Citation Information

Patent Citations

  • A method for preparing graphene

    CN104591178B

  • Swelling-resistant polyester composite film and preparation method and application thereof

    CN115447246B

  • High-strength high-toughness flame-retardant polypropylene composite material and preparation method thereof

    CN114085458A

  • Flame-retardant automotive carpet base cloth and preparation method thereof

    CN116695434A